MONTE SIÃO EXTREMIDADE DO SAFON: Estudo da influência da mitologia cananéia na Teologia de Sião a partir da análise exegética do Salmo 48 - Mendonça, élcio Valmiro Sales de (2012)
The Theology of Zion by the tradition of sons of Korah is somewhat curious. Tease is entertaining the idea of a canaanite influence in the Theology of Zion. There isn t denying that fact, because Psalm 48 seems to really have this influence. It is a canaanite influence and also the traditions of South Judahite. This research aims analyze the existing Theology of Zion in Jerusalem and presented in Psalm 48. This is to arrive at an answer about the influence that the sons of Korah may been the canaanite religion, using elements of canaanite myths in the composition of Psalm 48 and other psalms of this collection. Terms like Saphon, sea, death and Mount Zion, and concepts like mythology, sacred mountain, end of the world, Olympus, etc., make us think that really wanted to override the canaanite myths presenting a new reading from the faith in Yahweh. The sons of Korah had were North Israelite traditions, the cities where they lived were located in Ephraim, Manasseh and Dã. Some cities of Manasseh and Ephraim were canaanites cities. The kings of North were mostly promoter of the canaanite Religion. This was the environment where the sons of Korah lived and served your levitical minitstry.